Teaching efficacy beliefs of Ghanaian basic school teachers and their subject specializations - Philip Boateng; Ato Kwamina Arhin; Frank Owusu Sekyere; Asare Koto; Samuel Nti Adarkwah (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2019)
This study explores personal teaching efficacy beliefs of basic school teachers in Ghana undergoing recertification to upgrade their qualification. The study examines whether the personal teaching efficacy of the teachers is affected by their subject specialisation. A descriptive survey design was employed for the study. Data for the study was obtained from a total of 185 in-service teachers selected randomly from a group of teachers who were undergoing recertification from diploma to bachelor degree in basic education in a teacher education university in Ghana. Teacher Sense of Efficacy Scale (TSES) was adapted and used to measure in-service teachers' personal teaching efficacy beliefs. The findings of the study showed that in-service teachers have a high sense of personal teaching efficacy.  The study also revealed that in-service teachers' level of self-efficacy was not affected by their subject specialization.